CO oxidation over Au supported on Mn-ZSM5 and Mn-MOR - Zamaro, Juan Manuel (2015)
Active gold catalysts for CO oxidation were obtained by the deposition-precipitation of gold on ZSM-5 and mordenite, both of them ion-exchanged with manganese. A strong promotion of Mn upon the activity of bimetallic Au/Mn catalysts was observed when compared with the monometallic Au-zeolites. In turn, when an in-situ reduction of the bimetallic catalysts was performed, a further increase in activity was observed. Characterizations suggested that smaller gold nanoparticles were stabilized in the bimetallic solids and that the reduction process caused a rearrangement of Au and Mn species on the catalyst surface.